The BEG (PP2A-B55/ENSA/Greatwall) Pathway Ensures Cytokinesis follows Chromosome Separation - Cundell, M; Bastos, R; Zhang, T; Holder, J; Gruneberg, U; Novak, B; Barr, F (2013)
Cytokinesis follows separase activation and chromosome segregation. This order is ensured in budding yeast by the mitotic exit network (MEN), where Cdc14p dephosphorylates key conserved Cdk1-substrates exemplified by the anaphase spindle-elongation protein Ase1p. However, in metazoans, MEN and Cdc14 function is not conserved. Instead, the PP2A-B55α/ENSA/Greatwall (BEG) pathway controls the human Ase1p ortholog PRC1. In this pathway, PP2A-B55 inhibition is coupled to Cdk1-cyclin B activity, whereas separase inhibition is maintained by cyclin B concentration. This creates two cyclin B thresholds during mitotic exit. Simulation and experiments using PRC1 as a model substrate show that the first threshold permits separase activation and chromosome segregation, and the second permits PP2A-B55 activation and initiation of cytokinesis. Removal of the ENSA/Greatwall (EG) timer module eliminates this second threshold, as well as associated delay in PRC1 dephosphorylation and initiation of cytokinesis, by uncoupling PP2A-B55 from Cdk1-cyclin B activity. Therefore, temporal order during mitotic exit is promoted by the metazoan BEG pathway. © 2013 The Authors.